The Bioprospecting of Mangrove Red Snapper Cultivation (Lutjanus argentimaculatus Forsskål, 1775) Using Floating Cages - Angga Puja Asiandu; Achmad Gusti Malayudha (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2022)
Mangrove red snapper is one of the potential and valuable aquaculture products. The high demand for this fish causes high fishing activities. This condition can threaten their existence in the environment. It is necessary to have aquaculture activities to preserve their existence and meet market demand. Indonesia as a country with wide marine waters should be able to take advantage of the potential of fish farming by using a floating cage system. Thus, this article was written to analyze the bioprospecting of red snapper aquaculture. Based on the literature study, the floating net system has the potential to be developed on a large scale because the system has various advantages over fishing directly from nature. Things that must be considered in the cultivation of mangrove red snapper using floating nets are the area and quality of the floating nets, the composition of the feed, and the chemical components of the feed given to the fish. Based on economic potential, mangrove red snapper cultivation has high prospects which can be used as one of Indonesia's leading export products.